To simplify the expression \( 2(3v + 9) - 14 - 6(-5v - 4) \), we can follow these steps:
-
Distribute the 2 and -6: \[ 2(3v + 9) = 6v + 18 \] \[ -6(-5v - 4) = 30v + 24 \]
-
Substitute these back into the expression: \[ 6v + 18 - 14 + 30v + 24 \]
-
Combine like terms:
- Combine the \( v \) terms: \[ 6v + 30v = 36v \]
- Combine the constant terms: \[ 18 - 14 + 24 = 28 \]
-
Putting it all together, we get: \[ 36v + 28 \]
So the simplified expression is \( 36v + 28 \).
The correct response is: 36v+28 (36 v plus 28)